Saint Martha, Patron Saint of other People’s Homes - Grau-Dieckmann, Patricia (Eikón / Imago, 2017)
The story of Saint Martha is both paradoxical and touching. Represented in art with a broom and a ladle appointing her as housewife, she lives at the shadow of her siblings Maria of Bethany—Mary Magdalene— and the resurrected Lazarus. She is the silent woman who touches the hem of Jesus in the hope of curing her shameful menstrual bleeding. She is the one who must clean and cook while her spiritual sister —whom in the words of Jesus, “chooses the best part”— remains absorbed (and idle). After a painful agony, the main dramatic role of Martha in her own death was an undeniable fact, but her final act is stolen theatrically when an unexpected choir of angels conveys gloriously to heaven the soul of her sister. Saint Martha dies some days later, outdoors, humbly lying on the floor, with no angels and no music. She died the way she lived, with no stridency. Woman with no man, family, or home of her own, Martha the virgin is, paradoxically, venerated as the patroness of housewives.